PENGELOLAAN RISIKO KEWAJIBAN KONTIJENSI PEMERINTAH PADA PROYEK KPBU: Studi Kasus pada Jalan Tol Layang Jakarta-Cikampek II - Akhmadi, Muhammad Heru; Syaiban, Arkandisari Atmaja; Wati, Erlita Nurma (Indonesian Journal of Accounting and Governance, 2022)
The Public Private Partnership (PPP) is an alternative in the procurement of publicinfrastructure by involving the private sector in financing, processing and maintaining projects. InPPP projects there are guarantees that pose a contingent liability risk for the government. This articlediscusses the process of managing the risk of government contingent liabilities in the Jakarta-Cikampek II elevated toll road PPP project and looks for an appropriate alternative method totransfer the risk of government contingent liabilities to the private sector in the next project to reducethe burden of the government's contingent liabilities in the APBN. The research uses qualitativemethods by exploring opinions and analyzing perspectives from the Directorate of GovernmentSupport Management and Infrastructure Financing and the Directorate of State Financial RiskManagement as research objects through interview techniques. From the results of the study, it wasfound that risk management in this project uses a modified approach from the application of riskmanagement based on ISO 31000 and the process of managing the risk of government contingentliabilities in this toll road PPP project is optimal because all stages in the risk management processhave been carried out in accordance with the provisions in the regulations and the potential risk canbe minimized. In addition, three alternatives were found related to the method of transferring the riskof the government's contingent liabilities to other parties that can be applied to the next toll roadproject, namely the transfer of risk to a business entity on the condition that the business entity has riskinsurance, transferring all risks to PT. PII, as well as changing the form of cash compensation intocompensation for extension of the concession period or tariff adjustment, where each of these methodshas its own consequences.